1970
DOI: 10.1037/h0028401
|View full text |Cite
|
Sign up to set email alerts
|

Three biometrical genetic analyses of activity in the mouse.

Abstract: The classic, partial-classic, and diallel combining ability analyses were applied to behavioral measurements of activity and shock-elicited activity made on mice. The analyses for males indicated that additive but not dominant gene action influenced activity and significant general combining ability effects were present. The mode of inheritance of activity for females was more complex involving additive gene action and some specific combining ability effects. Shock-elicited activity was shown to be genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…These two outcomes may perhaps be attributable to the different strains and F 1 hybrids studied. In a study of shock-elicited activity in mice, Newell (1970) reported that F 1 hybrids from certain strains exhibited only additive effects, while other crosses revealed incomplete dominance and epistasis. There appears to be general agreement, however, that avoidance learning is characterized by either complete dominance or heterosis (see Collins, 1964;Schlesinger and Wimer, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…These two outcomes may perhaps be attributable to the different strains and F 1 hybrids studied. In a study of shock-elicited activity in mice, Newell (1970) reported that F 1 hybrids from certain strains exhibited only additive effects, while other crosses revealed incomplete dominance and epistasis. There appears to be general agreement, however, that avoidance learning is characterized by either complete dominance or heterosis (see Collins, 1964;Schlesinger and Wimer, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the same hybrid crosses may show heterosis in a given test and absence of vigor in another test (Winston, 1964). Similarly, in diallel studies, the specific combining activities of genotypes are more important than the general combining activities (Newell, 1970;Stasik, 1970). This is clearly evident in a study on alcohol preference in mice in which the A/J strain crossed with the low-alcoholpreference DBA resulted in offspring like DBA mice, but crossing with C3H yielded a phenotype practically identical with A/J (Fuller, 1964).…”
Section: Genetic Analysis Of Avoidance Maze and Wheel-running Behavio...mentioning
confidence: 99%
“…Although the transformations affected the relative magnitude of the parameters, heterosis was still found for activity, as well as potence for low variability on both measures and even the reciprocal 332 DAVID A. HAY differences in the F1 variances. Similarly, Newell (1970) found square root and natural log transformations had no effect on the detection of {d] and [Ii] and Copp and Wright (1952) reported that parent/offspring correlations were unaffected by a transformation, derived systematically from the data to meet the genetical criteria for scaling, namely homogeneity of variance among the non-segregating generations and absence of epistasis in the A, B and C scaling tests.…”
Section: J%tatural Selection and The Genetical Architecturementioning
confidence: 99%
“…Although it is therefore useful to be able to analyse the variances, the difficulty arises that, without rescaling, genotype-environmental interaction can alter the second-degree statistics, in the way described by Mather and Jinks (1971) and Perkins and Jinks (1970), to such an extent that unrealistic and even negative estimates of heritability may be obtained, e.g. Broadhurst and Jinks (1961) and Newell (1970). Some alternative methods based upon first-degree statistics are available (Jinks and Jones, 1958), and the technique described in the present paper where models are fitted to the generation means is capable of evaluating most forms of gene action, irrespective of whether or not the assumptions of scaling hold.…”
Section: Introductionmentioning
confidence: 99%